Fluid and food intake during professional men's and women's road-cycling tours - Ebert, T. R.; Martin, D. T.; Stephens, B.; McDonald, W.; Withers, R. T. (International Journal of Sports Physiology and Performance, 2007)
To quantify the fluid and food consumed during a men's and women's professional road-cycling tour. Methods: Eight men (age 25 ± 5 y, body mass 71.4 ± 7.4 kg, and height 177.4 ± 4.5 cm) and 6 women (age 26 ± 4 y, body mass 62.5 ± 5.6 kg, and height 170.4 ± 5.2 cm) of the Australian Institute of Sport Road Cycling squads participated in the study. The men competed in the 6-d Tour Down Under (Adelaide, Australia), and the women, in the 10-d Tour De L'Aude (Aude, France). Body mass was recorded before and immediately after the race. Cyclists recalled the number of water bottles and amount of food they had consumed. Results: Men and women recorded body-mass losses of ~2 kg (2.8% body mass) and 1.5 kg (2.6% body mass), respectively, per stage during the long road races. Men had an average fluid intake of 1.0 L/h, whereas women only consumed on average 0.4 L/h. In addition, men consumed CHO at the rate suggested by dietitians (average CHO intake of 48 g/h), but again the women failed to reach recommendations, with an average intake of ~21 g/h during a road stage. Conclusions: Men appeared to drink and eat during racing in accordance with current nutritional recommendations, but women failed to reach these guidelines. Both men and women finished their races with a body-mass loss of ~2.6% to 2.8%. Further research is required to determine the impact of this loss on road-cycling performance and thermoregulation.